The Professional Identity of Student Teachers from the Faculty of Education of the Catholic University of the Santísima Concepción in Chile - Jaramillo Azema, Cristian Alonso; Benoit Ríos, Claudine; Castro Cáceres, Ricardo (Revista Educación - Journal of Education, 2019)
This article presents the findings of a study that characterizes the professional identity of student teachers from the Faculty of Education at the Catholic University of Santísima Conception (UCSC) in Chile. The study had a qualitative and quantitative focus, thereby facilitating analysis of the origin of the attributes of the 107 participating student teachers. This qualitative study was complemented with quantitative data. Data analysis was triangulated following both a quantitative (analysis of the frequency) and qualitative (text analysis) logic. The findings underscore personal vocation and professional development as key factors required for defining professional identity. Once identified, it was possible to explain the relationship and pedagogical effect on students. It is concluded that student teachers develop their identities based on factors such as, personal vocation and a professional development process which is permanently linked.